2022
DOI: 10.1186/s13053-022-00221-5
|View full text |Cite
|
Sign up to set email alerts
|

Reflex BRCA1 and BRCA2 tumour genetic testing for high-grade serous ovarian cancer: streamlined for clinicians but what do patients think?

Abstract: Background Reflex (automatic) BRCA1 and BRCA2 (BRCA1/2) genetic testing of tumour tissue is being completed for all newly diagnosed high-grade serous ovarian cancer (HGSOC) in the province of Ontario, Canada. The objective of this study was to measure the psychological impact of tumour genetic testing among individuals with a new diagnosis of HGSOC. Methods Participants had a new diagnosis of HGSOC and received reflex BRCA1/2 tumour genetic testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
1
5
2
Order By: Relevance
“…32 The finding of overall high levels of satisfaction with genetic testing and an improved experience among older individuals is consistent with the prior literature on cancer genetic assessment. [32][33][34][35] Interestingly, although several prior studies have demonstrated that females are more likely to complete cascade testing than males, we found no difference in rates of testing by sex in our cohort 11,[36][37][38][39] ;…”
Section: Discussioncontrasting
confidence: 77%
“…32 The finding of overall high levels of satisfaction with genetic testing and an improved experience among older individuals is consistent with the prior literature on cancer genetic assessment. [32][33][34][35] Interestingly, although several prior studies have demonstrated that females are more likely to complete cascade testing than males, we found no difference in rates of testing by sex in our cohort 11,[36][37][38][39] ;…”
Section: Discussioncontrasting
confidence: 77%
“…Additional qualitative studies to glean participant perspectives may provide more context to the relatively high MICRA scores seen in our cohort; however, they may be related to consistently high levels of cancer-related distress, as cancer-related distress has been associated with genetic testing-related distress (McCuaig et al, 2022). (Bjornslett et al, 2015;Pozzar et al, 2022;Richardson et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
“…This is an exploratory secondary analysis of a prospective cohort study of newly diagnosed HGSOC patients seen at one of two academic centers in Toronto, Canada (McCuaig et al, 2022)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations